Central America [in State of the Climate in 2011] - Amador Astúa, Jorge Alberto (2012)
Large-scale climate patterns influenced temperature and weather patterns around the globe in 2011. In particu- lar, a moderate-to-strong La Niña at the beginning of the year dissipated during boreal spring but reemerged during fall. The phenomenon contributed to historical droughts in East Africa, the southern United States, and northern Mexico, as well the wettest two-year period (2010–11) on record for Australia, particularly remarkable as this follows a decade-long dry period. Precipitation patterns in South America were also influenced by La Niña. Heavy rain in Rio de Janeiro in January triggered the country’s worst floods and landslides in Brazil’s history. The 2011 combined average temperature across global land and ocean surfaces was the coolest since 2008, but was also among the 15 warmest years on record and above the 1981–2010 average. The global sea surface temperature cooled by 0.1°C from 2010 to 2011, associ- ated with cooling influences of La Niña. Global integrals of upper ocean heat content for 2011 were higher than for all prior years, demonstrating the Earth’s dominant role of the oceans in the Earth’s energy budget. In the upper atmosphere, tropical stratospheric temperatures were anomalously warm, while polar temperatures were anomalously cold. This led to large springtime stratospheric ozone reductions in polar latitudes in both hemispheres. Ozone concentrations in the Arctic strato- sphere during March were the lowest for that period since satellite records began in 1979. An extensive, deep, and persistent ozone hole over the Antarctic in September indicates that the recovery to pre-1980 conditions is proceeding very slowly